The association between hyponatraemia and long-term functional outcome in patients with aneurysmal subarachnoid haemorrhage: A single centre prospective cohort study. (August 2020) - Quinn, Liam; Tian, David H.; Fitzgerald, Emily; Flower, Oliver; Andersen, Chris; Hammond, Naomi; Davidson, Keryn; Delaney, Anthony
Highlights: Hyponatraemia occurs in approximately 50% of patients following aSAH. Hyponatraemia is not associated with an increase in the odds of a poor long-term functional outcome following aSAH. Hyponatraemia is associated with prolonged ICU and hospital length of stay. Abstract: To assess the association between hyponatraemia and long-term functional outcome and other relevant outcomes in patients with aneurysmal subarachnoid haemorrhage (aSAH) we conducted a prospective cohort study in a Neurosciences Intensive Care Unit (ICU) in Sydney, Australia. The primary exposure variable was hyponatraemia (Na + <135 mmol/L). The primary outcome was favourable outcome, a score of 5–8 on the extended Glasgow Outcome Score (GOSe) at 12 months. We also measured mortality, the incidence of delayed cerebral ischaemia (DCI) and cerebral arterial vasospasm and duration of ICU and hospital admission. There were 200 participants, 111 (56%) developed hyponatraemia. Hyponatraemia was not associated with favourable outcome at 12 months (unadjusted odds ratio [OR] OR 1.31, 95% confidence interval [CI] 0.65–2.65, p = 0.56). The result was similar after adjustment for baseline covariates (adjusted OR 0.60, 95% CI 0.16–1.99, p = 0.43). There was no association between hyponatraemia and the incidence of DCI (OR 0.95, 95% CI 0.46 to 2.0, p > 0.99) nor cerebral arterial vasospasm (OR 1.4, 95% CI 0.8 to 2.5, p = 0.27). Those who developed hyponatraemia had a longer median duration of ICU admission (17 days, interquartile range [IQR] 12 to 20, compared to 13 days, IQR 8–21, p = 0.02) and longer median duration of hospital admission (24 days, IQR 21–30, compared to 22 days IQR 14–31, p = 0.05). While hyponatraemia is common following aSAH, it is not associated with worse long-term functional outcome, increased rate of DCI, nor cerebral arterial vasospasm. Hyponatraemia in patients with aSAH was associated with longer duration of ICU and hospital admission.